The Administrative Costs of Local Government Property-Based User Charges and Their Regressivity - Helena Blažić; Sandra Stašić; Saša Drezgić (Central European Public Administration Review)
The paper measures the administrative costs (assessment and collection costs) of immovable property user charges in local governments in Croatia. This study represents a small scale survey comprising mostly small local governments. First, we establish their costs structure and then we compare the cost-revenue ratio with their size. As expected, the administrative costs of the analyzed user charges turned out to be regressive in regards to the size of local governments. The results imply that substitution of those different charges would be beneficial for local government budgets. In order to mitigate the problem we propose several alternatives: one general tax/charge; amalgamation of the smallest local governments or referring to assessment and collection of user charges in small local governments to the larger/mutual unit.